Cosmic Rays and their Connections to Earth's Climate - Rodrigues, André Massafferri (Cadernos de Astronomia, 2025)
There is now a consensus among scientists that human contribution to greenhouse gas emissions has caused a significant increase in global temperature over the last century, with simulations indicating an increase of around 5.0°C by 2100. In these models, cloud dynamics contribute the greatest uncertainties. Although the process is based on a relatively well-known chain, from aerosols evolving into condensation nuclei to macroscopic clouds, the role of ionic induction promoted by cosmic rays as a possible intensifier of nucleating processes in the atmosphere remains inconclusive. Recent research carried out at the particle physics laboratory, CLOUD/CERN, despite the difficult task of emulating the atmosphere in the laboratory, has yielded results that motivate its study in a real system, as in the Brazilian project CRE4AT (Cosmic Ray Experiment for Atmosphere).
Keywords: cosmic rays; cloud formation; climate